2009
DOI: 10.1088/1674-4527/9/4/009
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between CME velocities and X-ray fluxes of associated flares

Abstract: Coronal mass ejection (CME) velocities have been studied over recent decades. We present a statistical analysis of the relationship between CME velocities and X-ray fluxes of the associated flares. We study two types of CMEs. One is the FL type associated only with flares, while the other is the intermediate type associated with both filament eruptions and flares. It is found that the velocities of the FL type CMEs are strongly correlated with both the peak and the time-integrated X-ray fluxes of the associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
1
10
0
2
Order By: Relevance
“…The fastest CMEs are associated with the strongest flares. This relation has been presented by other authors (Moon et al, 2003;Burkepile et al, 2004;Maričič et al, 2007;Chen and Zong, 2009;Bein et al, 2012) and is also observed in our sample of events (Figure 2, left). It is worth noticing that CMEs connected with the slow LDEs are very fast.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The fastest CMEs are associated with the strongest flares. This relation has been presented by other authors (Moon et al, 2003;Burkepile et al, 2004;Maričič et al, 2007;Chen and Zong, 2009;Bein et al, 2012) and is also observed in our sample of events (Figure 2, left). It is worth noticing that CMEs connected with the slow LDEs are very fast.…”
Section: Resultssupporting
confidence: 92%
“…Relationships between flares and CMEs, e.g. SXR flux vs. CME velocity, duration of the flare rising phase vs. duration of the acceleration phase, were investigated by many authors (Zhang et al, 2001;Moon et al, 2003;Burkepile et al, 2004;Vršnak, Sudar, and Ruždjak, 2005;Maričič et al, 2007;Chen and Zong, 2009;Berkebile-Stoiser et al, 2012). Zhang et al (2001) investigated the temporal relationship between CMEs and associated solar flares.…”
Section: Introductionmentioning
confidence: 99%
“…One factor is the filament and its material drainage. As the evidence for this, if filament-associated CME events are excluded, the relation between the CME speed and the flare intensity is significantly increased (Chen and Zong, 2009). Another major factor might be the restraining force of the background field overlying the CME, as proposed by Török and Kliem (2007), who found that a steep decay of the background field with height leads to a fast CME and a gentle decay leads to a slow CME.…”
Section: Should Fast and Slow Cmes Be Attributed To Different Models?mentioning
confidence: 85%
“…It can be seen that there is a linear correlation between them, with the corresponding linear correlation coefficient 0.66, which is above the 95% level of confidence. However, the plot of these data also displays considerable scatter (see the discussion by Chen & Zong 2009). Both CMEs and flares may be produced by quite different mechanisms (Feynman & Hundhausen 1994) or the same mechanism but two different components of explosive magnetic-energy release (Jain et al 2010).…”
Section: Parameterizing Solar Sarsmentioning
confidence: 99%